2019
DOI: 10.1186/s13643-019-1030-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise on cardiometabolic outcomes in women with polycystic ovary syndrome not taking the oral contraceptive pill: protocol for a systematic review and meta-analysis

Abstract: Background Polycystic ovary syndrome (PCOS) is the most common endocrinopathy, affecting 4–12% of reproductive-aged women. Women with PCOS often exhibit many metabolic abnormalities that are associated with an increased cardiovascular disease (CVD) risk, independent of obesity. Exercise interventions from 12 to 24 weeks have been shown to have positive effects on blood lipid profile, ovulation and insulin resistance in women with PCOS. However, no consensus on which exercise interventions are effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous studies have supported the superior health benefits of vigorous exercise compared to moderate exercise in the PCOS population, which, however, is clear in the literature about the effectiveness of aerobic training in managing clinical improvements in the health parameters in women with PCOS population. In addition, the lack of a combined intervention (i.e., HIIT + diet) and questions involving the different phenotypes of PCOS (A-D) may have interfered with the responses to physical exercises (Woodward et al, 2019;Patten et al, 2020). Frontiers in Physiology frontiersin.org…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have supported the superior health benefits of vigorous exercise compared to moderate exercise in the PCOS population, which, however, is clear in the literature about the effectiveness of aerobic training in managing clinical improvements in the health parameters in women with PCOS population. In addition, the lack of a combined intervention (i.e., HIIT + diet) and questions involving the different phenotypes of PCOS (A-D) may have interfered with the responses to physical exercises (Woodward et al, 2019;Patten et al, 2020). Frontiers in Physiology frontiersin.org…”
Section: Resultsmentioning
confidence: 99%
“…The review is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines and was pre-registered in the International Prospective Register of Systematic Reviews (PROSPERO): CRD42018086117. The full protocol is described elsewhere [22].…”
Section: Methodsmentioning
confidence: 99%
“…Several systematic reviews have been conducted on the efficacy of metformin or exercise training on outcomes in PCOS including reproductive implications, metabolic dysfunction, and cardiovascular risk [20][21][22][23]. However, there is currently no systematic review evaluating the effects of metformin in addition to exercise in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%